Mudharabah as a Conduit for Social Cohesion among Vulnerable Women - Fareiny Morni; Azima Khan (The Postgraduate of Institut Agama Islam Negeri Metro Lampung, 2020)
The focus of this research is specified to the interlinkages between three concepts i.e. social cohesion, women’s economic empowerment and mudharabah investments. Instead of microfinancing, this paper explores the possibility of utilizing mudharabah as a tool in uplifting vulnerable societies, especially women and promote social cohesion in the surrounding community. We explore the importance and value that empowering women economically can bring to improving the cohesiveness of a society and whether mudharabah can be used to achieve this. A case study method was used to highlight existing models used by NGOs to provide assistance to vulnerable women. However, existing models are found to be limited to the funds available in the organization and in turn, this restricts the aid that the NGO are able to give out. A mudharabah model would help NGOs to outsource funding to individuals and institutions who can contribute capital to women and uplift them from their current economic condition. With that this paper proposes a two-tier mudharabah structure as an alternative financing model which can be used as a conduit for circulation and distribution of wealth in a society. This structure is found to be financially viable and limits the capital providers’ losses to the amount of their contribution.